Construction and testing of the Gentrification Worldview Instrument. Issue 4 (7th August 2020) - Mullenbach, Lauren E.; Baker, Birgitta L.; Mowen, Andrew J.
ABSTRACT: Primary data collection that is generalizable and applicable on a large scale would benefit gentrification research, as more stakeholders' perspectives could be gathered. Thus, an instrument measuring gentrification worldview was constructed and tested for inter-item relationships, through survey pretesting, exploratory factor analysis, and confirmatory factor analysis. The Gentrification Worldview Instrument (GWI) is a set of evaluative beliefs representing one's worldview of gentrification. Items measure beliefs about neighborhood change and the roles of individual residents and local government in preserving or changing city neighborhoods. The instrument demonstrated partial measurement invariance across two racial groups. The resulting models indicate the GWI is composed of three domains, neighborhood preservation, development, and social integration . The instrument provides researchers, policy makers, and communities with a tool to measure people's perceptions of gentrification, which can then be used to predict attitudes and behaviors.